Evaluation of Tzanakis scoring system in acute appendicitis: a prospective study - Lakshminarasimhaiah, Arun Kumar S.; A. L., Nagaraja; M., Srinivasaiah (International Surgery Journal, 2017)
Background: Tzanakis scoring system is a combination of clinical evaluation, ultrasonography and laboratory marker of inflammatory response, used as accuracy of diagnosis of acute appendicitis. Objective of this study was to evaluate the predictability of Tzanakis scoring system in preoperative diagnosis of acute appendicitis and compare its accuracy with histopathological examination (HPE). Methods: A prospective non-randomized study was designed to study those patients who suspected clinically as acute appendicitis, admitting to Department of General Surgery, ESIC-MC PGIMSR, Bangalore between November 2013 to July 2015. After complete clinical examination, radiological and laboratory investigations Tzanakis score was calculated and patients with score 8 or >8 underwent appendicectomy and HPE results were analyzed. Results: Out of 218 participants, 200 patients underwent emergency appendicectomy and were selected for the study. The sensitivity and specificity of Tzanakis score was 85.49% and 71.43% respectively. The overall diagnostic accuracy was 85% with positive predictive value of 98.80% and negative value of 15.15%. Conclusions: Tzanakis scoring system is an effective modality in the establishment of accuracy in diagnosis of acute appendicitis, but the limitation is observer bias which may vary the scoring system.